Phosphorylation status of matrix metalloproteinase 2 in myocardial ischaemia–reperfusion injury. Issue 8 (7th March 2012) - Sariahmetoglu, Meltem; Skrzypiec-Spring, Monika; Youssef, Nermeen; Jacob-Ferreira, Anna Laura B; Sawicka, Jolanta; Holmes, Charles; Sawicki, Grzegorz; Schulz, Richard
Abstract : Objective: To investigate whether alterations in the phosphorylation status of matrix metalloproteinase 2 (MMP-2) in the heart may be protective in the setting of ischaemia–reperfusion (IR) injury. Design: In-vitro heart function and biochemical research study. Setting: University basic science laboratory. Interventions: Male Sprague–Dawley rats, weighing 250–350 g. Isolated rat hearts were perfused at constant pressure either aerobically for 75 min or subjected to 20 min of global, no-flow ischaemia followed by 30 min of reperfusion. Main Outcome Measures: Heart mechanical function, MMP-2 activity and troponin I levels. Results: The serine/threonine phosphatase inhibitor okadaic acid (OA) improved the recovery of mechanical function compared with control IR hearts and prevented the loss of troponin I. OA significantly reduced protein phosphatase 2A, but not protein phosphatase 1, activity in perfused hearts. IR stimulated the activation and release of MMP-2 into the coronary effluent in the first 2 min of reperfusion. This was accompanied by a decrease in the remaining activity and protein level of MMP-2 in heart tissue determined at the end of the reperfusion. OA did not alter the IR-stimulated release of MMP-2 into the coronary effluent, but reduced the decrease in MMP-2 in reperfused hearts. The immunoprecipitation of heart homogenates using anti-phosphoserine antibody showed that MMP-2 is phosphorylated. The dephosphorylation of MMP-2 by alkaline phosphatase treatment of homogenates prepared from IR hearts treated with OA significantly increased MMP-2 activity. Conclusions: These results suggest that the phosphorylation status of MMP-2 is important in its contribution to myocardial IR injury.